2019
DOI: 10.3389/fimmu.2019.02450
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cellular and Tissue HIV Reservoirs With Toll-Like Receptor Agonists

Abstract: The elimination of both cellular and tissue latent reservoirs is a challenge toward a successful HIV cure. “Shock and Kill” are among the therapeutic strategies that have been more extensively studied to target these reservoirs. These strategies are aimed toward the reactivation of the latent reservoir using a latency-reversal agent (LRA) with the subsequent killing of the reactivated cell either by the cytotoxic arm of the immune system, including NK and CD8 T cells, or by viral cytopathic mechanisms. Numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 191 publications
(189 reference statements)
2
51
0
Order By: Relevance
“…The key challenge to cure for HIV-1 infection is represented by the more extensively studied therapeutic strategies known as "Shock and kill". These strategies are aimed toward the reactivation of the latent reservoir using a latency-reversal agent (LRA) with the subsequent killing of the reactivated cell either by the cytotoxic arm of the immune system, including NK and CD8 T cells, or by viral cytopathic mechanisms [155,156]. Borducchi et al show that administration of the V3 glycan-dependent bNAb PGT121 together with GS-9620 during ART delayed viral rebound following discontinuation of ART in simianehuman immunodeficiency virus (SHIV)-SF162P3infected rhesus monkeys in which ART was initiated during early acute infection [157].…”
Section: Pyrimidine and Purine Base Derivativesmentioning
confidence: 99%
“…The key challenge to cure for HIV-1 infection is represented by the more extensively studied therapeutic strategies known as "Shock and kill". These strategies are aimed toward the reactivation of the latent reservoir using a latency-reversal agent (LRA) with the subsequent killing of the reactivated cell either by the cytotoxic arm of the immune system, including NK and CD8 T cells, or by viral cytopathic mechanisms [155,156]. Borducchi et al show that administration of the V3 glycan-dependent bNAb PGT121 together with GS-9620 during ART delayed viral rebound following discontinuation of ART in simianehuman immunodeficiency virus (SHIV)-SF162P3infected rhesus monkeys in which ART was initiated during early acute infection [157].…”
Section: Pyrimidine and Purine Base Derivativesmentioning
confidence: 99%
“…TCR/CD3 inertness was not the only functional consequence of the molecular changes that can occur in host cells of latent HIV-1 infected T cells. While we do not detail this phenomenon, we found that TLR pathway signaling can also be impaired (Figure 3), which would have implications for efforts to identify HIV-1 reactivating agents that address the TLR/Myd88 pathway [52][53][54][55][56]. Given that our data detail the dysfunctional nature of latently HIV-1 infected T cells, and the seemingly random nature of observed changes, it needs to be assumed that the further upstream a NF-B activating pathway is targeted, the less likely it is that an efficient, HIV-1 reactivating NF-B signal is being triggered.…”
Section: Discussionmentioning
confidence: 99%
“…This was also observed at the population level, where flagellin stimulation only triggered HIV-1 reactivation in a fraction of the latently HIV-1 infected T cell population ( Figure 3H). Changes to the host cell signaling network that were induced during HIV-1 infection thus may not be limited to the TCR/CD3 signaling pathway and extend to other activating receptors/pathways that are currently investigated as targets of latency reversing agents (LRA) [52][53][54][55][56].…”
Section: Generation Of Cd3-responsive and Cd3-inert Latently Hiv-1 Inmentioning
confidence: 99%
“…After binding to their ligands, the TLRs commonly induce activation of NF-κB, AP1 and various interferon regulatory factors (IRFs). Many TLR agonists are now being evaluated as potential LRAs, with agonists of TLR3, TLR7 and TLR9 already advancing into human trials [99]. MGN1703, a TLR9 agonist, induced HIV plasma RNA in 6 of 15 study participants concomitant with increased activation of NK and CD8 T cells, but no reduction in latent reservoir size was observed [100].…”
Section: Toll-like Receptor (Tlr) Agonistsmentioning
confidence: 99%